Faktor-Faktor yang Berhubungan dengan Tingkat Kepatuhan dalam Menjalani Pengobatan pada Penderita Hipertensi - Apriliani, Tri; Suraya, Izza (Politeknik Baubau, 2024)
Treatment adherence is an important factor in controlling blood pressure in hypertensive sufferers, this is necessary to minimize the occurrence of complications. Cases of hypertension are one of the priority problems that occur at the Pakuhaji primary health care. However, it is not yet known the level of adherence to treatment of hypertension sufferers there. This study aims to determine the related factors with the level of adherence in undergoing treatment for hypertensive patients at Pakuhaji primary health care in 2023. This type of research is quantitative analytic with a cross-sectional study design. The sample was selected using a purposive sampling technique of 134 respondents. Data collection was carried out by interviewing using a questionnaire. The analysis used in this study is univariate and bivariate analysis using the Chi Square Test. Bivariate test results show the variables age (Pvalue = 1.000), gender (Pvalue = 1.000), education level (Pvalue = 0.068), employment status (Pvalue = 0.336), income level (Pvalue = 0.047), family support (Pvalue = 0.355 ), the role of health workers (Pvalue = 0.287), health literacy (Pvalue = 0.047), and level of knowledge (Pvalue = 0.000). The research results found factors that were related to the level of compliance in undergoing treatment for hypertension sufferers at the Pakuhaji primary health care in 2023, namely income level, level of knowledge, and health literacy.